Adiposity Omics and Molecular Understanding - Oxholm Gordeladze, Jan (IntechOpen, 2017)
This book is the second in a series of two, featuring the Adiposity - Omics and Molecular Understanding, serving as an introduction to modern views on how the adipocytes are reciprocally interacting with organ systems in order to explain the biology of the body's fat cells and how they are integrated with other organ systems, like muscle cells and the liver, in order to control the lipid metabolism in our bodies, to finally preserve a positive balance between white and brown/beige adipocyte tissues (WAT and BAT). The understanding of the "omics" of obesity will therefore enable clinicians and researchers to better pursue the untoward incidents of metabolic deviations from a defined and health-bringing homeostasis, with fully responding WAT and BAT, being able to preserve a healthy balance between fat-producing and fat-metabolizing tissues for the benefit of the host, and thus longevity (optimal health with healthy, well-functioning organ systems) throughout a lifetime.